116 Analysis of histopathological features, molecular results and serum tumour markers in cases of fallopian tube involvement by metastatic gastrointestinal adenocarcinoma. (13th November 2020) - Basha Mohamed, M; Haider, A; Arora, R
Abstract : Introduction: Ovarian metastasis from non-gynaecological primary has been the focus of many studies with little attention given to tubal involvement. We present an analysis of tubal involvement by gastro-intestinal tract primary, the most common non-gynaecological metastasis to the adnexa. Methods: We evaluated cases of gastro-intestinal tract metastasis involving the fallopian tube over 5 years for histological patterns of involvement, molecular data and serum tumour markers. Results: Of the 12 cases which met the inclusion criteria, 2/12 cases (16.7%) had no prior history of gastro-intestinal adenocarcinoma. The metastatic adenocarcinoma involved the right tube in 3/12 cases (25%), left tube in 3/12 cases (25%), and bilateral tubes in 6/12 cases (50%). Ovary was also involved in all but one case. Tubal fimbrial end was involved in 3/12 cases (25%). The metastasis had a flat mucosal pattern in 4/12 cases (33.3%); resembling mucinous metaplasia and serous tubal intraepithelial carcinoma (STIC). Other patterns seen were: extracellular mucin pools in 6/12 cases (50%), individual glands/cells in 6/12 cases (50%) and tumour sheets in 5/12 cases (41.7%). Mismatch repair proteins were retained in all 9 cases in which they were tested. Next generation sequencing detected mutations in 6/12 cases (50%), with KRAS being the most common mutation. Serum CA125 was raised in 6/10 cases (60%), CEA in 9/12 cases (75%) and CA19.9 in 3/10 cases (30%). Conclusion: Awareness of various patterns of tubal involvement by metastatic gastro-intestinal adenocarcinoma is important to avoid misdiagnosis especially as the serum tumour markers can be variable.